Revisiting development of the green bond market: Evidence of the ahp approach - Chuc Anh Tu; Tapan Sarker; Ehsan Rasoulinezhad (Asian Development Bank Institute (ADBI), 2020)
Green bonds (GBs) are a fresh and applicable financial instrument introduced with the purpose of funding environmental projects. In the last years, the development of GBs has shown that this is an effective investment channel for the purpose of protecting the environment. Viet Nam is an Asian economy that has been trying to establish and develop a GB market. The aim of this study is to find out what are the most important factors influencing development of the GB market in Viet Nam. To this end, we use the analytic hierarchy process to analyze the opinions of experts. The main results reveal that the most important influencing factors are the legal framework for GB operations, monetary policies of Viet Nam's central bank, and the official interest rate of GB. In other words, infrastructural and economic factors are the most important requirements to develop the current GB market in Viet Nam. We recommend establishing green regulations and green economic policies in the country to support the implementation of GBs in Viet Nam.
Keywords: N0; N10; O10; O23; 330; sustainable development; green bond; analytic hierarchy process